(untitled) (The Peerian Journal, 2022)
Within the framework of copyright, rights holders enter into agreements with persons using works (objects of copyright and related rights) on their behalf on the basis of the powers granted by collective management organizations; the collection, distribution, and payment of fees to copyright holders have also been studied in detail. Attention is paid to some current issues related to the improvement of this institution, international standards of copyright protection and comparative analysis of national legislation, as well as the views of scientists from Uzbekistan and other countries. Suggestions and recommendations of scientific and practical importance for the development of copyright were put forward.